2006
DOI: 10.1080/13814780600757153
|View full text |Cite
|
Sign up to set email alerts
|

Do influenza and acute respiratory infective diseases weigh heavily on general practitioners’ daily practice?

Abstract: During the winter there is an increased work-load for GPs due to the diffusion of influenza virus and respiratory tract diseases. "Burn out syndrome" is increasing among the GPs. Territorial GPs' action is highly efficacious. Patients self-certification should be evaluated. Vaccine therapy could be more effective if done on a larger population. More research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 5 publications
2
22
0
1
Order By: Relevance
“…From a limitations perspective, individuals who did not receive medical attention for their ARI were not recruited, thus results are not necessarily generalizable to all influenza illness cases in the community. From a measurement perspective, variations of the ARI symptom severity metric used in this study have been used in numerous other investigations [30-38] and have been previously correlated with influenza positive status [19] and viral shedding [20], but have not been formally validated and remain a subjective measure of symptom perceptions that may be subject to recall and self-presentation biases, as is common with some other self-reported metrics [39]. This is a particular concern in some subgroup comparisons where symptom severity expectations may vary as a result of perceptual priming during study enrollment (e.g., different beliefs on how influenza vaccination should impact symptoms).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a limitations perspective, individuals who did not receive medical attention for their ARI were not recruited, thus results are not necessarily generalizable to all influenza illness cases in the community. From a measurement perspective, variations of the ARI symptom severity metric used in this study have been used in numerous other investigations [30-38] and have been previously correlated with influenza positive status [19] and viral shedding [20], but have not been formally validated and remain a subjective measure of symptom perceptions that may be subject to recall and self-presentation biases, as is common with some other self-reported metrics [39]. This is a particular concern in some subgroup comparisons where symptom severity expectations may vary as a result of perceptual priming during study enrollment (e.g., different beliefs on how influenza vaccination should impact symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of seasonal influenza symptoms compared to non-influenza ARI has not been extensively studied though. One study reported an association between increased symptom severity in patients with laboratory confirmed 2009 pandemic influenza compared to seasonal influenza [18]; limited evidence also suggests that influenza ARI may be more severe than ARI due to other causes [19]. In an influenza challenge study, symptom severity was associated with increased magnitude of influenza virus shedding [20].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the extra workload of influenza patients puts pressure on the primary care service during epidemics, and this is added to normal activity [10]. General practices in Norway generally pre-book appointments and have a few available appointments for acute illnesses every day.…”
Section: Introductionmentioning
confidence: 99%
“…Upper respiratory tract infections result in an estimated increase of 12.5% in patient visits per month during cold and flu season. 19 In the United States, direct medical costs related to the common cold (physician visits, secondary infections and medications) were an estimated $17 billion a year in 1997. 17 Indirect costs owing to missed work because of illness or caring for an ill child were an estimated $25 billion a year.…”
mentioning
confidence: 99%